KONSEP EPIDEMIOLOGI TERJADINYA PENYAKIT COVID-19 DI INDONESIA - Putra Apriadi Siregar; Jelita Suryani Siregar, Sheila Megarani, Putri Suci Ramadiah, Muhammad Khair Gunawan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Corona virus disease 2019 or COVID-19 was first reported in Wuhan, China in late 2019. COVID-19 belongs to the genus Betacoronavirus, the Anasilis results provide similarities to SARS. After further investigation, a novel strain of coronavirus was identified as the cause. The 2019 Novel Coronavirus (2019-nCoV) was officially named Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-two). So far, COVID-19 has spread to all countries in the world, so its status was declared as a pandemic by the World Health Organization on March 11, 2020. This article aims to determine the descriptive epidemiology of COVID-19 in Indonesia and to find out the latest updates related to COVID-19. This research method uses a cross- sectional study design study conducted in April - May 2023. The sample for this study was taken from the total population (total sampling) of 252 people. The outcome of this article is to explain the latest updates on epidemiology, virology, transmission, clinical symptoms, diagnosis, management, risk factors and prevention of COVID-19